Catastrophic pediatric sports injuries - Luckstead, E. F.; Patel, D. R. (Pediatric Clinics of North America, 2002)
The high school sports of wrestling, gymnastics, ice hockey, baseball, track, and cheerleading should receive closer attention to prevent injury. Safer equipment and sport-specific conditioning should be provided and injuries strictly monitored. Greater attention must also be paid to swimming and diving techniques, and continued observation is needed for heat stroke and heat intolerance in sports such as football, wrestling, basketball, track and field, and cross-country. An increased awareness of commotio cordis in sports other than baseball should include ice hockey, football, track field events, and lacrosse. American football because of the sheer numbers and associated catastrophic injury potential must continue to be monitored at the highest medical levels!